The Vγ9Vδ2 T cell antigen receptor and butyrophilin 3 A1 (BTN3A1): Models of interaction, the possibility of co-evolution, and the case of dendritic epidermal T cells - Karunakaran, Mohindar Murugesh; Herrmann, Thomas (Frontiers in Immunology, 2014)
Most circulating human gamma delta T cells are Vγ9Vδ2 T cells. Their hallmark is the expression of T cell antigen receptors (TCR) whose γ-chains show a Vγ9-JP (Vγ2-Jγ1.2) rearrangement and are paired with Vδ2 containing δ-chains, a dominant TCR configuration, which until recently seemed to occur in primates only. Vγ9Vδ2 T cells respond to phosphoantigens (PAg) such as (E)-4-Hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP) which is produced by many pathogens and isopentenyl pyrophosphate (IPP) which accumulates in certain tumors or cells treated with aminobisphosphonates such as zoledronate. A prerequisite for PAg-induced activation is the contact of Vγ9Vδ2 T cells with cells expressing butyrophilin 3 A1 (BTN3A1). We will first critically review models of how BTN3 might act in PAg-mediated Vγ9Vδ2 T cell activation and then address putative co-evolution of Vγ9, Vδ2 and BTN3 genes. In those rodent and lagomorphs used as animal models all three genes are lost but a data base analysis showed that they emerged together with placental mammals. A strong concomitant conservation of functional Vγ9, Vδ2 and BTN3 genes in other species suggests co-evolution of these three genes. A detailed analysis was performed for the new world camelid alpaca (Vicugna pacos). It provides an excellent candidate for a non-primate species with presumably functional Vγ9Vδ2 T cells since TCR rearrangements share features characteristic for PAg-reactive primate Vγ9Vδ2 TCR and proposed PAg-binding sites of BTN3A1 have been conserved. Finally, we analyze the possible functional relationship between the butyrophilin-family member Skint1 and the γδ TCR-V genes used by murine dendritic epithelial T cells (DETC). Among placental mammals, we identify 5 rodents, the cow, a bat and the cape golden mole as the only species concomitantly possessing potentially functional homologues of murine Vγ3, Vδ4 genes and Skint1 gene and suggest to search for DETC like cells in these species.